Investigation into the microscopic mechanism underlying formation damage induced by the reinjection of oil-bearing wastewater - Tang, Chao; Du, Ke; Guan, Gongshuai; Gai, Xiangfu; Li, Guo; Li, Qingsong; Wang, Lichao; Guo, Hongguang; Sun, Wenping; Gao, Chao; Xu, Weiwei; Lu, Zhuoyuan; et al. (Frontiers in Earth Science, 2025)
The reinjection of treated oilfield water into formations stands as one of the commonly employed methods in oilfield water injection development. However, certain treated waters contain a substantial number of suspended oil droplets, which can lead to the blockage of flow paths and pore channels. At present, there is a deficiency in experimental verification results regarding the reinjection of oily wastewater, and a lack of a reasonable explanation for the micro-mechanism underlying oil droplet migration. Consequently, in order to elucidate the distribution characteristics of oil droplets and the microscopic mechanism of oil droplet migration during the process of oilfield treatment water reinjection, a simulated oil and microfluidic chip were fabricated to conduct relevant experiments. The experimental results reveal that the particle size of oil droplets is the most crucial control indicator affecting reservoir blockage, with a porosity damage rate of 21.9% and a permeability damage rate of 20.9%. The results further indicate that large oil droplets directly block the pores, while small oil droplets blocking the pores exhibit two regional characteristics: saturated blockage and unsaturated blockage. Additionally, the numerical simulation results are in agreement with the experimental findings. This study offers a framework for the implementation of wastewater reinjection in oilfield operations.